A prática de alfabetização no primeiro ano do ensino fundamental: um estudo de caso em uma escola pública municipal - Cheruti, Luciana Josélia Corrêa (2015)
This study is inserted in a research line called “Teachers formation, teaching practice and theory” of the postgraduate program in education of La Salle University and analyzes the correlation among the legal aspects, MEC (Ministry of Education and Culture) guidelines and the literacy practice, in the first year of an elementary school in the city of Novo Hamburgo. The main theoretical contributions used, come from authors such as: Piaget (1990), Vygotsky (1994), Freire (2001), Ferreiro e Teberosky (1999), Mortatti (2000), Soares (2003), Nóvoa (2006) and Arroyo (2007). This work has a qualitative methodological nature, using a case study. The data collection has taken place in a public school in the city of Novo Hamburgo, through semi-structured interviews, observations and notes in a field diary. The data analysis was carried out based on analysis proposed by Bardin (1988). During the research, it has been verified that there is a gap between the speech and the literacy practice in regards to the elementary school. It was perceived the attention of the teacher in prioritize the literacy process through playfulness. It was noticed that the teacher emphasizes what regards to the social disparities and to the families literacy universe leading to difficulties to the acquisition of reading and writing material. However, it was found that although the school gave the resources and a good ambience they were not used in a way to explore the whole opportunities that they gave. It was concluded, along the research, that there are plenty of gaps between the speeches and the pedagogical actions, as well as a detachment between the theory and literacy practice in the elementary school. Due to these understandings, it follows that there is still a lot to be searched and reflected about the subject, and that more studies concerning these matters should be carried out.